A latent profile analysis of callous-unemotional traits and emotional behavioural problems in early childhood: associations with self-regulation - Tan, Chloe Yi En (2024)
Studies have used a person-centred approach to examine profiles of callous-unemotional traits with conduct problems in early childhood. Yet, there is a lack of research exploring heterogeneity of profiles with callous-unemotional traits and internalizing problems, though they often co-occur. The current study addressed this gap and explored the heterogeneity of profiles by examining their relations to children’s self-regulation, which may inhibit the onset of conduct problems. Parents of age 6–7 children (n = 475; 48% female) from Singapore’s birth cohort study completed the Inventory of Callous-Unemotional Traits and Child Behavior Checklist. First, Latent Profile Analysis was conducted to delineate profiles of callousness and uncaring traits (CA/UN) with externalizing (EX) and internalizing problems (IN) in early childhood. Next, a one-way ANOVA assessed differences in children’s global self-regulation across the identified profiles, using parents’ responses on the Behaviour Rating Inventory of Executive Function 2 when children were 7. Four profiles emerged: low risk (34%; low on both CA/UN and IN/EX), medium risk (51%; medium levels of CA/UN/IN/EX), mixed risk (7%; low CA/UN but high IN/EX), and high risk (8%, high on both CA/UN and IN/EX). While high risk group exhibited the lowest self-regulation, the mixed risk group displayed lower levels of self-regulation than the low risk but higher than the medium risk group. This is the first study to use a person-centred approach in examining different manifestations of callous-unemotional traits with emotional behavioural problems in early childhood. Findings show how heterogeneity between the profiles identified could be associated with children’s self-regulation.